Molecular differences in IDH wildtype glioblastoma according to MGMT promoter methylation - Keßler, Tobias; Sahm, Felix; Sadik, Ahmed; Stichel, Damian; Berberich, Anne; Reifenberger, Guido; Zacher, Angela; Sabel, Michael; Tabatabai, Ghazaleh; Steinbach, Joachim; Sure, Ulrich; Krex, Dietmar; et al. (Neuro-Oncology, 2018)
AbstractBackground. O6-methylguanine-DNA-methyltransferase (MGMT) promoter methylation status is a predictive biomarker in glioblastoma. We investigated whethe